On the number of limit cycles in discontinuous piecewise linear differential systems with two pieces separated by a straight line - Euzebio, Rodrigo D. [UNESP]; Llibre, Jaume (Elsevier B.V., 2015)
In this paper we study the maximum number N of limit cycles that can exhibit a planar piecewise linear differential system formed by two pieces separated by a straight line. More precisely, we prove that this maximum number satisfies 2 <= N <= 4 if one of the two linear differential systems has its equilibrium point on the straight line of discontinuity. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Non-smooth differential system; Limit cycle; Piecewise linear differential system